2011
DOI: 10.1507/endocrj.k10e-152
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte zinc concentration as an indicator to distinguish painless thyroiditis-associated transient hypothyroidism from permanent hypothyroidism

Abstract: There are two clinical presentations of hypothyroidism, permanent hypothyroidism (PH) and transient hypothyroidism (TH). PH patients require a lifelong T4 supplementation. In contrast, TH spontaneously resolves within several months and therefore TH patients basically need no or short-term supplementation. abstract. Red blood cell (RBC) zinc (Zn) concentration reflects a patient's mean thyroid hormone level over the preceding several months. The aim of this study was to examine whether RBC Zn level can be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Levels of T4 or T3 fluctuating between the upper and lower normal range are indicative of subclinical thyroid status, suggesting that the metabolic rate was influenced rather than a balance rhythm. It was demonstrated that the erythrocyte zinc concentration is reflective of the mean thyroid hormone level over the preceding several months (19) . However, these results are not widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of T4 or T3 fluctuating between the upper and lower normal range are indicative of subclinical thyroid status, suggesting that the metabolic rate was influenced rather than a balance rhythm. It was demonstrated that the erythrocyte zinc concentration is reflective of the mean thyroid hormone level over the preceding several months (19) . However, these results are not widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Kuriyama et al 41 demonstraram que concentrações séricas de zinco eritrocitário são mais baixas em pacientes com tireoidite transitória em relação aos pacientes com tireoidite permanente. Os autores sugeriram que a dosagem sérica de zinco eritrocitário pode ser útil para distinguir essas patologias e, assim, evitar a suplementação desnecessária de T4.…”
Section: Zincounclassified